Multi-agent Approach to Fault Tolerant Control Systems – A Conceptual Model to the Industrial Internet of Things - Mendes, Mário J. G. C. (2019)
A general concern in industrial world is related to process maintenance, safety and functionality problems in the presence of faults. Most industrial processes are very large, complex and with communication networks. Because of size and complexity, it is very dificult to conceive a diagnostic system and ensure the availability of the entire process. Sometimes, malfunctions or simple performance deterioration of equipments or processes occur, forcing to production interruptions. Thus, it is fundamental in the industrial world of the 21st century - Industry 4.0 - to have Fault Tolerant Control systems that provides faults information to some kind of control reconfiguration system that will try to accommodate the faults, maintaining the process operation with a minimal degradation in the production or allowing a controlled plant shut down. This work presents a conceptual model to be applied in the Industrial Internet of Things world.